Reconceptualising Maqāṣid al-Sharī‘ah as an Instrument of Tarjīḥ - Andi Ali Akbar; Muhammad Sirojudin Sidiq; Anggita Vela; Ahmad Yajid Baidowi (FiTUA: JURNAL STUDI ISLAM, 2026)
Maqāṣid al-sharī‘ah are the fundamental objectives underpinning every provision of Islamic law. However, in classical tarjīḥ practice, the maqāṣid are often treated merely as ethical and normative principles and have not yet been operationalised methodologically in the assessment and selection of legal evidence. This study aims to reconceptualise maqāṣid al-sharī‘ah as a methodological foundation in the process of tarjīḥ in Islamic law, particularly in responding to contemporary challenges such as interpretative pluralism, demands for justice, and the dynamics of social change. This study employs a qualitative-descriptive approach through a literature review and content analysis of classical texts, such as the works of al-Ghazālī, al-Shāṭibī, and Ibn ʿĀshūr, as well as the contemporary thought of Jasser Auda and Mohammad Hashim Kamali. The research findings indicate that maqāṣid al-sharī‘ah not only function as normative values but can also be operationalised as practical instruments in the process of tarjīḥ. The maqāṣidī approach enables a more comprehensive selection of dalīl by holistically considering public interest, social impact, and the alignment of the dalīl with the objectives of sharia. This study offers a systemic and multidimensional conceptual model of maqāṣidī tarjīḥ as a contribution towards the renewal of Islamic legal methodology (istinbāṭ) to make it more contextual and relevant.